Kondo Box Effects by Varying Coupling between Dots and Chain (Bulletin of Pure and Applied Sciences – Physics, 2019)
We have studied the Kondo box effect by varying the coupling between the dots and  the chain. The physics of a Kondo box can be realized in systems of two impurities  coupled between them by a finite number of non-interacting sites. Finite size effects  can take place together with a magnetic interaction between the impurities of the  Ruderman-Kittel-Kasuya-Yosida type. We have found that when Kondo effect is  present, the fourth order Ruderman-Kittel-Kasuya-Yosida interaction between the  impurities is mediated by the electrons of the non-interacting sites, which are  participating simultaneously in the Kondo screening of each impurity. It was also  found that other types of magnetic interactions arised such as the Kondo correlated or  super exchange interactions. Using vibrational wave functions it was predicted that  the interaction between the impurities was mainly due to an interference-enhanced  hybridization that generated Kondo doublet states. We analysed a double quantum  dot system simultaneously connected to metallic leads and between themselves  through a finite number of non-interacting sites. The impurities in such as system are  coupled to and interact through a non-interacting linear chain that consisted a  quantum box, whose electrons participated in the Kondo’s screening. Thus there is  interplay between a bulk continuous Konodo regime and a two impurity Kondo box.  We also analysed the transport properties for different values of number of sites of the  non-interacting linear chain and for different couplings of the quantum dots with it.  The results were valid for temperatures below the characteristic single impurity  Kondo temperature. The obtained results were in good agreement with previously  obtained results